1993
DOI: 10.1002/eqe.4290220902
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization of human walking observed during lateral vibration of a congested pedestrian bridge

Abstract: Observation of human‐induced large‐amplitude lateral vibration of an actual pedestrian bridge in an extremely congested condition is reported. Walking motions of pedestrians recorded by a video camera are analysed. It is found that walking among 20 per cent or more of the pedestrians on the bridge was synchronized to the girder lateral vibration. With this synchronization, the total lateral force from the pedestrians to the girder is evidently increased and it acts as a resonant force on the girder lateral vib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
143
0
5

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 245 publications
(154 citation statements)
references
References 6 publications
6
143
0
5
Order By: Relevance
“…Moreover, it has been observed that the relationship between increasing the amount of load and the number of people is not linear. The dynamic load depends of the synchronization of crowd [8][9][10]. The synchronization increases with visual contact and the influence of noise in the public [11][12].…”
Section: Effect Of Human-structure Interactionmentioning
confidence: 99%
“…Moreover, it has been observed that the relationship between increasing the amount of load and the number of people is not linear. The dynamic load depends of the synchronization of crowd [8][9][10]. The synchronization increases with visual contact and the influence of noise in the public [11][12].…”
Section: Effect Of Human-structure Interactionmentioning
confidence: 99%
“…This model, conceived for footbridges vibrating in the vertical direction, was tested on a laterally vibrating footbridge by Fujino et al (1993): the model underestimated the structural response, since it is not conceived to account for human-structure interaction.…”
Section: Action Of Groups and Crowdsmentioning
confidence: 99%
“…The observation of videos is also a way of measuring crowd density and velocity. For example, the T-bridge in Japan (Fujino et al, 1993;Yoshida et al, 2007), which connects a stadium to a bus terminal, was instrumented with three cameras installed on the stadium roof, synchronised between each other and connected to a computer (Figure 11). Thanks to an ad hoc-conceived digital head-tracking system, the motions of 50 pedestrians have been identified and compared with the lateral motion of the deck.…”
Section: In Situ Tests and Observationmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on large lateral vibrations induced by the synchronous walking of pedestrians in the cable-stayed bridge (T-bridge) was first investigated in 1993, and the mechanism of lateral vibrations was clarified [2]. Moreover, the same large lateral vibrations in the stress ribbon pedestrian bridge (London Millennium Bridge) were reported in 2000 [3].…”
Section: Introductionmentioning
confidence: 99%